Clinician beliefs and attitudes about home haemodialysis: a multinational interview study. Issue 6 (12th December 2012) - Tong, Allison; Palmer, Suetonia; Manns, Braden; Craig, Jonathan C; Ruospo, Marinella; Gargano, Letizia; Johnson, David W; Hegbrant, Jörgen; Olsson, Måns; Fishbane, Steven; Strippoli, Giovanni F M
Abstract : Objectives: To explore clinician beliefs and attitudes about home haemodialysis in global regions where the prevalence of home haemodialysis is low, and to identify barriers to developing home haemodialysis services and possible strategies to increase acceptance and uptake of home haemodialysis. Design: Semistructured interviews, thematic analysis. Setting: 15 dialysis centres in Italy, Portugal, France, Germany, Sweden and Argentina. Participants: 28 nephrologists and 14 nurses caring for patients receiving in-centre haemodialysis. Results: We identified four major themes as being central to clinician beliefs about home haemodialysis in regions without established services: external structural barriers (ready access to dialysis centres, inadequate housing conditions, unstable economic environment); dialysis centre characteristics (availability of alternative treatments, competing service priorities, commercial interests); clinician responsibility and motivation (preserving safety and security, lack of awareness, knowledge and experience, potential to offer lifestyle benefits, professional interest and advancement); and cultural apprehension (an unrelenting imposition, carer burden, attachment to professional healthcare provision, limited awareness). Conclusions: Despite recognising the potential benefits of home haemodialysis, clinicians practicing in Europe and South America felt apprehensive and doubted the feasibility of home haemodialysis programmes. Programmes that provide clinicians with direct experience of home haemodialysis could increase acceptance and motivation for home-based haemodialysis, as might service prioritisation and funding models that favour home haemodialysis.